Evaluation of environmental policy instruments : a case study of the Finnish pulp & paper and chemical industries - Hildén, Mikael; Lepola, Jukka; Mickwitz, Per; Mulders, Aard; Palosaari, Marika; Similä, Jukka; Sjöblom, Stefan; Vedung, Evert (Finnish Environment Institute, 2013)
This research-based evaluation of environmental policy Instruments in Finland is focussed on regulatory instruments based on the Water Act, the Air Pollution Control Act and the Chemicals Act, on electricity taxation and on voluntary environmental management systems. The examined policy instruments have had several positive effects. They have directed major industrial point source polluters towards solving environmental problems. The transparency has been an important factor ensuring the success of the policy instruments and in avoiding the regulatory capture that could have thrived in a system largely based on negotiations between operators and authorities. The transparency has made it easy for Finnish firms to adopt environmental management systems and an open attitude to environmental reporting. The permit conditions have not directly resulted in innovations, but they have contributed to the diffusion of end-of-pipe technology and have contributed to innovations by expanding the market for environmentally better technical solutions. The permit systems have also indirectly contributed to innovations by creating a demand for environmental experts and environmental education.Networks have clearly developed as a consequence of and in response to regulatory instruments. These networks appear to have had their greatest significance prior to the permit procedures. The trend has been towards a greater emphasis of the communication in the networks prior to the presentation of an application in order to ensure a smoothly functioning permit process. In the networks contributing to innovations and the diffusion of innovations authorities have largely been outsiders, except when an innovation has become a de facto standard for permit conditions.The different kind of effects, the complexity of consequences and the uncertainties with respect to causes and effects mean that studies aiming at evaluating the overall worth and merit of an environmental policy instrument should never be structured from a single point of view ...